Assessment of quality of life of stroke survivors and their caregivers presenting to a tertiary care hospital in Pakistan - Rehman, Awais Ur; Niazi, Rauf; Rehman, Hassan Ur; Javed, Ayesha (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the quality of life of stroke survivors and their caregivers presenting to tertiary care setup. Method: The descriptive study was conducted from July to December 2019 at the Neurology Department, Pakistan Institute of Medical Sciences, Islamabad, Pakistan, and comprised patients of either gender with ischemic or haemorrhagic stroke aged 40-70 years and their caregivers. Data was collected using the stroke-specific quality of life Scale and the caregiver quality of life questionnaire. Data was analysed using SPSS 20. Results: Of the 80 patients, 50(62.5%) were males and 30(37.5%) were females. The overall mean age was 61.46±11.80 years, and 56(70%) were aged >55 years. Among the patients, speaking power, mobility and mood were more affected with mean levels of 15.51±8.63, 22.63±8.33 and 19.08±7.05, respectively. The domains of social role, self-care and upper extremity function were also affected with mean values of 19.022±7.06, 15.71±8.81 and 18.88±7.02, respectively. Among the caregivers, the levels physical wellbeing and functional wellbeing were high 15.07±5.65 and 15.35±5.76, respectively. There were differences in terms of age and gender but the difference was not significant (p>0.05). Conclusion: The quality of life of stroke survivors was low, and that of caregivers was also quite compromised. Key Words: Haemorrhagic stroke, Ischemic stroke, Caregivers, Quality of life, SSQOL, CQLQ, Stroke survivors.